Comparison of anal and rectal swabs in the diagnosis of anorectal gonorrhoea in women. Issue 3 (June 1979) - Kolator, B; Rodin, P
Abstract : Among 228 women with gonorrhoea (confirmed by culture), swabs taken blindly from the anal canal gave positive results in 26.3% and those taken from the rectum under direct vision in 27.6%. Swabs from both sites gave positive results in 23.2% of patients, from the anal canal alone in 3.1%, and from the rectum alone in 4.4%. Thus, culuture of anal canal swabs seems to give as reliable results as rectal swabs when proctoscopy cannot be carried out.